2006
DOI: 10.1895/wormbook.1.72.1
|View full text |Cite
|
Sign up to set email alerts
|

Cell division

Abstract: The C. elegans embryo is a powerful model system for studying the mechanics of metazoan cell division. Its primary advantage is that the architecture of the syncytial gonad makes it possible to use RNAi to generate oocytes whose cytoplasm is reproducibly (typically >95%) depleted of targeted essential gene products via a process that does not depend exclusively on intrinsic protein turnover. The depleted oocytes can then be analyzed as they attempt their first mitotic division following fertilization. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 70 publications
1
117
0
Order By: Relevance
“…As with yeast, we observed that none of the analyzed genes enhanced the lethality of the him-10(e1511ts)/NUF2 kinetochore component mutant ( Table 1), suggesting that the identified enhancers have a specific effect on the SAC pathway. The interaction data for mdf-1, mdf-2, and san-1 support previous findings that some synthetic interactions that are common to MAD1 and MAD2 are not shared by MAD3 ( Y54G9A.6/BUB3 enhances the lethality of SAC mutants: Next we tested a putative ortholog of the kinetochore-associated component Bub3, Y54G9A.6 (which we will refer to as bub-3; reviewed in Oegema and Hyman 2006;Stein et al 2007;Tarailo et al 2007), for genetic interaction with SAC mutants. bub-3(RNAi) animals do not display any obvious phenotypes ( Figure 2B); however, depletion of BUB-3 in the absence of MDF-1, MDF-2, or SAN-1 results in a significant decrease in viability, presumably due to elevated chromosome instability (Figure 2).…”
supporting
confidence: 76%
“…As with yeast, we observed that none of the analyzed genes enhanced the lethality of the him-10(e1511ts)/NUF2 kinetochore component mutant ( Table 1), suggesting that the identified enhancers have a specific effect on the SAC pathway. The interaction data for mdf-1, mdf-2, and san-1 support previous findings that some synthetic interactions that are common to MAD1 and MAD2 are not shared by MAD3 ( Y54G9A.6/BUB3 enhances the lethality of SAC mutants: Next we tested a putative ortholog of the kinetochore-associated component Bub3, Y54G9A.6 (which we will refer to as bub-3; reviewed in Oegema and Hyman 2006;Stein et al 2007;Tarailo et al 2007), for genetic interaction with SAC mutants. bub-3(RNAi) animals do not display any obvious phenotypes ( Figure 2B); however, depletion of BUB-3 in the absence of MDF-1, MDF-2, or SAN-1 results in a significant decrease in viability, presumably due to elevated chromosome instability (Figure 2).…”
supporting
confidence: 76%
“…This pronuclear meeting occurs during centration and is also dependent on long microtubules and the dynein heavy chain subunit in C. elegans (DHC-1) (32,33). Therefore, if the genes specifically required for the centrosome centration anchor are inhibited, the meeting of the male and female pronuclei occurs, but the nucleus-centrosome complex does not reach the cell center.…”
Section: Resultsmentioning
confidence: 99%
“…We decided to use the C. elegans embryo as a model system because of its stereotypical first mitotic division. Analyzing the consequences of depleting essential chromosome components is also straight-forward in this system because RNAi can be used to generate oocytes reproducibly Ͼ95% depleted of targeted proteins that can be monitored as they progress through their first mitotic division after fertilization (22). During this division, mitotic prophase initiates when the oocyte and sperm-derived pronuclei are on opposite sides of the embryo and continues as the pronuclei migrate toward each other.…”
Section: Resultsmentioning
confidence: 99%